E-DEMOCRACY IN INDONESIA: USE OF SOCIAL MEDIA AND CHALLENGES IN ENCOURAGING YOUTH POLITICAL PARTICIPATION - Mustofa, Mustabsyirotul Ummah; Utama, Rafif Sakti; Andalus, Mutia Kartika (JWP (Jurnal Wacana Politik), 2024)
A survey released by CSIS in September 2022 showed an increase in internet access for young voters from 2018 to 2022. The survey release showed a significant increase in access to social media as a source of information for young voters 19.5 per cent. Moreover, the CSIS survey found a condition where the interest of young Indonesians is currently very low in politics. On the other hand, hoaxes and misinformation can threaten young voters if they are not equipped with adequate political literacy and understanding. This desk study research was conducted to get an explanation from existing literature of how to utilise social media as a medium for the development of e-democracy amidst young people’s antipathy towards politics. Healthy social media free from intervention and arbitrariness of government policies can be a medium for young people’s political participation to foster e-democracy. The results of the desk study show that social media is possibly a means of political participation for youth and at the same time provides space for the growth of e-democracy with the prerequisite that the government is not abusive and offensive towards the use of digital media in Indonesia. This shows empirically that growing e-democracy needs not only a technological medium but a regime policy that supports e-democracy because digital media has become a living space attached to today’s young generation.